Human-Computer Interactive English Learning From the Perspective of Social Cognition in the Age of Intelligence - Yan, Qilin (Frontiers in Psychology, 2022)
Under the wave of globalization, the ties between countries are getting closer and closer. Based on the differences in the languages of different countries, the importance of English as a universal language is becoming more and more prominent. In the past, English teaching was mainly taught by teachers and students. This mode of English learning is more of theoretical teaching, which has little effect on improving English ability. In the era of intelligence, with the upgrading of technology and the renewal of ideas, interactive English teaching is more accepted by people and becomes a new solution for English teaching. Studying English teaching from the perspective of social cognition, this paper proposes to realize human-computer interaction with the help of advanced science and technology, create an interactive teaching environment, and realize interactive learning in an English environment. The experimental results of this paper show that human-computer interactive English teaching can help enhance students' interest in English learning and improve English expression significantly.